Evaluation of time to sputum smear conversion and its association with treatment outcomes among drug-resistant tuberculosis patients: a retrospective record-reviewing study - Alzarea, Abdulaziz Ibrahim; Saifullah, Amna; Khan, Yusra Habib; Alanazi, Adullah Salah; Alatawi, Ahmed D.; Algarni, Majed Ahmed; Almalki, Ziyad Saeed; Alahmari, Abdullah K.; Alhassan, Hassan H.; Mallhi, Tauqeer Hussain (Frontiers in Pharmacology, 2024)
Background: This study examined the time to sputum smear and culture conversion and determinants of conversion, as well as variables associated with treatment outcomes among drug-resistant pulmonary tuberculosis (DR-PTB) cases. Methods: The electronic database and written medical records of patients were utilized to assess the sociodemographic, clinical, microbiological, and treatment characteristics and outcomes of study participants. Results: Among 736 patients with pulmonary tuberculosis (PTB), the mean age was 36.5 ± 16.5 years, with males comprising 53.4% and a mean weight of 47.76 ± 11.97 kg. The median time period for sputum smear conversion and sputum culture conversion was a month. The first-month culture conversion (p < 0.001, aOR = 5.817, and 95% CI = 3.703–9.138) was the determinant of sputum smear conversion and receiver operating curve analysis with AUC = 0.881, 95% CI = 0.855–0.907, and p < 0.001, which showed a high level of predictive ability for the regression model for the initial sputum smear conversion. However, the first-month sputum conversion (p < 0.001, aOR = 7.446, and 95% CI = 4.869–11.388) was attributed to sputum culture conversion, and the model has shown excellent predictive ability for regression with ROC curve analysis demonstrating AUC = 0.862, 95% CI = 0.835–0.889, and p < 0.001. A total of 63.2% of patients showed favorable treatment outcomes, with 63.1% of cases achieving treatment-cured status. The previous use of SLD, history of smoking, duration of illness ≤ 1 year, extensively drug-resistant tuberculosis, and first-month sputum conversion were the variables attributed to favorable treatment outcomes observed in drug-resistant pulmonary tuberculosis cases. ROC curve analysis with AUC = 0.902, 95% CI = 0.877–0.927, and p < 0.001) has shown outstanding ability for regression model prediction for the variables influencing treatment outcomes. Conclusions: Within 2 months of treatment, most patients had converted their sputum cultures and sputum smears. The determinants of early sputum smear and sputum culture conversion, as well as favorable treatment outcomes, were identified. These factors should be considered during the design and implementation of effective strategies for drug-resistant tuberculosis control programs.